2019
DOI: 10.1002/ajh.25603
|View full text |Cite
|
Sign up to set email alerts
|

Predicting venous thromboembolism in multiple myeloma: development and validation of the IMPEDE VTE score

Abstract: Venous thromboembolism (VTE) is a common cause of morbidity and mortality among patients with multiple myeloma (MM). The International Myeloma Working Group (IMWG) developed guidelines recommending primary thromboprophylaxis, in those identified at high‐risk of VTE by the presence of risk factors. The National Comprehensive Cancer Network (NCCN) has adopted these guidelines; however, they lack validation. We sought to develop and validate a risk prediction score for VTE in MM and to evaluate the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 56 publications
8
100
0
2
Order By: Relevance
“…Thus, we found great interest in the article by Sanfilippo et al reporting on the first risk assessment score, the IMPEDE VTE score in order to evaluate VTE risk in newly diagnosed MM (nMM) starting any chemotherapy. 2 We strongly agree with the author's perspective. Indeed, MM does require specific management because of the common use of corticosteroids like dexamethasone and agents such as immunomodulatory drugs (IMiDs) which increase the risk of VTE.…”
supporting
confidence: 73%
“…Thus, we found great interest in the article by Sanfilippo et al reporting on the first risk assessment score, the IMPEDE VTE score in order to evaluate VTE risk in newly diagnosed MM (nMM) starting any chemotherapy. 2 We strongly agree with the author's perspective. Indeed, MM does require specific management because of the common use of corticosteroids like dexamethasone and agents such as immunomodulatory drugs (IMiDs) which increase the risk of VTE.…”
supporting
confidence: 73%
“…Three risk groups were identified, and the respective six-month cumulative incidence of VTE following treatment initiation was 3.3% for the low-risk group (scores ≤3), 8.3% for intermediate-risk group (score of 4-7), and 15.2% for the high-risk group (≥8 score). The score was externally validated using the Surveillance, Epidemiology, End Results (SEER)-Medicare database and 4256 MM patients [88]. A second group also developed a clinical RAM for MM patients who receive IMiD-based regimens using the same database to extract data retrospectively; 2397 patients with MM were selected initially using the SEER database, and the data were subsequently validated using the Veterans registry.…”
Section: Risk Assessment Modelsmentioning
confidence: 99%
“…It should be pointed out that a previous history of arterial or venous thromboembolism was an exclusion criteria for the two studies [36] comparing the three different approaches (ASA, LMWH and warfarin) as possible prophylaxis in IMiDs treated patients, that formed the basis for the formulation of the IMGW guidelines. Indeed, new studies have indicated that a previous VTE is the strongest indicator of the probability of developing VTE [51] and, in fact, one of our patients who developed VTE during EloRd had actually a history of VTE as the only risk factor; in these patients, ASA might be not enough to provide an adequate thrombo-prophylaxis [51].…”
Section: Discussionmentioning
confidence: 88%
“…All the most recent literature recognizes the need to give a different weight to the different risk factors. In this perspective, a new proposed score, the IMPEDE VTE score [51], that assigns different points to different risk factors, has been recently proposed. It has the merit of dividing patients in three categories with different risk of developing VTE.…”
Section: Discussionmentioning
confidence: 99%